Analysis of Company Size, Profitability, and Solvency on Firm Value at BUMN IDX20 - Yudhi Prasetiyo (Formosa Journal of Science and Technology, 2022)
This research was conducted to test and determine the factors that affect the value of the company. This study also uses company size and two main factors in financial performance, namely profitability, and solvency. Profitability uses the return on equity (ROE) indicator in its measurement, and solvency uses debt to total assets (DTA) in its measurement. This study uses a quantitative method with the help of the IBM SPSS Statistic 25 tool in processing the results of data calculations, then the sample used is the IDX20 state-owned company listed on the Indonesian stock exchange for the 2018-2021 period by using the purposive sampling method as the population selection in this study. The results of this study found that the size of the company has a significant positive effect on the value of the company, then the financial performance of profitability which is proxied in return on equity gives results with no effect on the firm value and solvency which is indicated by a debt to total assets which shows the results which have a significant negative effect on firm value.